PENERAPAN PAJAK PENGHASILAN ORANG PRIBADI DARI PERDAGANGAN VALUTA ASING SECARA ONLINE YANG MENGGUNAKAN BROKER LUAR NEGERI - Zuhdi Arman; Lenny Husna (Fakultas Hukum, Universitas Samudra, 2020)
Foreign exchange trading is one of the most popular businesses in the world, including the Indonesian people. The income generated from an Indonesian trader will certainly raise an aspect of Income Tax that must be fulfilled. This study aims to analyze the application of personal income tax and to determine the form of tax avoidance that can occur in relation to online foreign exchange trading using foreign brokers. The method used in this research is descriptive qualitative, data collection is done by means of in-depth interviews, observation and documentation, informant selection techniques with purposive sampling, data analysis techniques performed by data reduction, data presentation and drawing conclusions. The result of this research is the application of personal income tax on personal traders (taxpayers) which is carried out by means of a self-assessment system with the expectation of voluntary compliance in which the taxpayer must self-report the tax owed at the end of the year. Due to the lack of supervision over the implementation of the self assessment system, and online forex trading transactions are carried out fully online, taxpayers have a very big opportunity to do tax evasion. In the application of individual PPh, there are also several obstacles that occur both from the side of the taxpayer itself and from the side of the government.